"A Brave New (Digital) World"? Effects of in-House Social Media on HRM. (February 2013) - Hauptmann, Stefan; Steger, Thomas
Social media offer many opportunities for organizations but present, at the same time, many challenges, too. Particular attention must be paid to the new patterns of behavior emerging in organizations. We argue that these patterns derive both from the technical characteristics of the virtual environment and also from specific social structural conditions currently emerging. By referring to two case studies, we want to highlight and discuss the implications of these current developments and their opportunities, threats and consequences for Human Resource Management. Our analysis will be supported by theories and research on the reproduction of rules and norms, on the one hand, and on social structural studies about digital natives and Generation Y, on the other. In order to sharpen our argument and to highlight the challenges of social media for human resource management, we propose the concept and notion of a 'parallel world.'